Running-intensity fluctuations in elite rugby sevens performance - Furlan, N.; Waldron, M.; Shorter, K.; Gabbett, T. J.; Mitchell, J.; Fitzgerald, E.; Osborne, M. A.; Gray, A. J. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To investigate temporal variation in running intensity across and within halves and evaluate the agreement between match-analysis indices used to identify fluctuations in running intensity in rugby sevens.